PERFORMANCE EVALUATION OF DRIP IRRIGATION SYSTEM ACCORDING TO THE SUGGESTED STANDARDS - & AL-DULAIMY, AL-MHMDY (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiment was conducted during autumn season 2017 at Al-Saqlawia, far about 50km north-west of Baghdad/Iraq, aimed to a periodic evaluation for drip irrigation system to obtain best values of the suggested standards. The experiment included two factors; first, emitters’ discharge (d) at two levels using emitters with 4Lh-1 design discharge (d4) and emitters with 8Lh-1 design discharge (d8). While the second factor; operational pressure at three levels, first level, operational pressure 0.5 bar(P1), second, operational pressure 0.7 bar(P2), and the last, operational pressure 1.0 bar (P3), the experiment was designed according to randomized complete block design. The results showed a decrease in values of both uniformity coefficient and emission uniformity, while the rate of actual discharge and variation ratios have been increased with the increase of operational pressure and for both discharge, where the reduction ratios at uniformity coefficient reached 3.02%, 4.25%, while at emission uniformity 6.52%, 7.18%, then actual discharge ratios increased about 10.75%, 20.25%, while the discharge variation ratios increased to reach 389.36%, 490.48%; while at depending an emitter 8Lh-1 actual discharge, the reduction ratios at uniformity coefficient reached 1.33%, 2.64%, then at emission uniformity, they reached 3.91%, 2.85%, while actual discharge ratios increased to reach 11.73%, 21.44%, then the increase ratios of discharge variation were about 122%, 199.22% when comparing above values with the effect of operational pressure mentioned previously.